Imagery and imaginary of islander identity: Older people and migration in Irish small-island communities - Vanessa Burholt (Journal of Rural Studies, 2013)
This paper examines the imagery and imaginaries of islander identity and makes an original contribution to the fields of gerontology and nissology. Drawing on data collected through in-depth interviews with 19 older residents of two small-island communities located off the island of Ireland, we address the central roles played by older people in creating and sustaining islander identities. Reflecting both public and private representations of islander identity, the paper contrasts an island ‘imagery’ with an island ‘imaginary’, resulting in a complex ‘imag(in)ery’ of islander identity. This paper explores three main themes. To what extent do older residents of island communities perceive an ‘imag(in)ery’ of islander identity? In what ways do older islanders contribute to, substantiate or perpetuate the imag(in)ery of the islander identity? Are there alternative imag(in)eries of the islander identity for different groups of older people who live in island communities? Our analysis identified two imag(in)eries of islander identity. An historical islander identity was structured by the shared hardships and enforced self-sufficiency associated with residence in remote communities. Contemporary islander identities are founded on the positively perceived isolation of islands, an historical and cultural sense of belonging, frequent social interaction within cohesive, safe and secure communities, and a persistence of ‘traditional’ values. Older people were actively engaged in the (re)production of islander identity such as helping visitors discover their island origins, producing traditional cultural artefacts, passing knowledge of culture down through the generations, and acting to maintain the civic life of the island community. Knowledge of local and traditional skills imbued some older islanders with the ability to perform island-specific symbolic rituals. Our study revealed subtle forms of differentiation between over-arching categories of island residents based on migration histories. In particular, older people’s narratives revealed a hierarchy in relation to claims to islander status.